MODERN ISSUES OF DEVELOPING INNOVATIVE PRODUCTS IN COMMERCIAL BANKS - Denis Gennadevich Lovyannikov; Nadezhda Sergeevna Lovyannikova (Вестник Северо-Кавказского федерального университета, 2022)
This article describes the major ways for introducing innovation in the banking system. There is also a view on the specific features of organizational types of managing innovation in banks. The article also shows and offers a rationale for the innovation strategy role and their management trends. There is an analysis of the impact that the financial crisis has had on the implementation of innovation in banking (dynamics of attracting funds to the banking system).